Lithium Cyanide Supported by O‐ and N‐Donors. Issue 3 (20th December 2016) - Budanow, Alexandra; Franz, Klaus‐Dieter; Vitze, Hannes; Fink, Lothar; Alig, Edith; Bolte, Michael; Wagner, Matthias; Lerner, Hans‐Wolfram
Abstract : A series of adducts of LiCN, namely [Li(Me2 CO3 )CN], [Li(Et2 CO3 )CN], and [Li(NMP)CN] (NMP = N ‐methyl‐2‐pyrrolidone) were prepared by treatment of solvent‐free LiCN with the appropriate donor. The starting material for these approaches, donor‐free LiCN, was quantitatively prepared from Me3 SiCN and Li[Me] in diethyl ether at 0 °C. Alternatively, [Li(NMP)CN] was synthesized by metathesis reaction of LiCl with NaCN in the presence of stoichiometric amounts of NMP. Although [Li(Me2 CO3 )CN] and [Li(Et2 CO3 )CN] are water‐sensitive compounds and decompose at the exposure to air, [Li(NMP)CN] is stable in air, even at elevated temperatures. The thermal stability of [Li(NMP)CN] was proven by differential thermal analysis (DTA). [Li(NMP)CN] shows thermal stability up to temperatures of about 132 °C. To evaluate the cyanation ability the reactions of 1‐bromooctane and 3‐bromocyclohexene with unsupported LiCN, [Li(NMP)CN], and a mixture of NaCN/LiCl/NMP were investigated. We found that [Li(NMP)CN] as well as LiCl/NaCN/NMP are efficient cyanation reagents comparable to the expensive and air‐sensitive, donor‐free LiCN. A product of the chloride‐cyanide‐bromide exchange could be isolated and structurally characterized by X‐ray diffraction. Abstract :